A cross-sectional study on occupational exposure to airborne azoxystrobin in tomato greenhouses post-spraying - Rocco MANGIFESTA; Luca COPPETA; Piergiorgio ASTOLFI; Teresa GALANTI; Luca DI GIAMPAOLO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2024)
Introduction: The global demand for year-round vegetable production has intensified the use of pesticides in greenhouse farming, posing potential health risks to agricultural workers. This study investigates the levels of Azoxystrobin, a widely used fungicide, in the air inside a tomato greenhouse following its application, aiming to assess the occupational exposure risks during and after the critical re-entry period. Methods: Airborne particulate matter and volatile organic compounds (VOCs) were measured at two strategic locations inside the greenhouse: along the external rows (PP1) and the central area (PP2). Sampling was conducted 48 hours post-application (T0) and two months later during the harvesting phase (T1). DustTrak DRX and PhoCheck Tiger devices were used for real-time monitoring of particulate matter and VOCs, respectively. Statistical analyses, including the Wilcoxon signed-rank and Mann-Whitney U tests, were performed to evaluate the differences in concentrations over time and between locations. Results: At T0, significantly higher concentrations of particulate matter were detected at PP2 compared to PP1, with total dust levels surpassing the 10% Threshold Limit Value (TLV) at PP2. VOC concentrations at the plants (PP3) exceeded exposure limits, placing them in the “high” risk category, while VOC levels further from the plants (PP4) were within the “average” risk range. By T1, both particulate and VOC concentrations had significantly decreased, reducing exposure levels to below the low-risk threshold. Discussion: The findings underscore the substantial exposure risks associated with re-entry into greenhouses following pesticide application, revealing that elapsed time alone may not be sufficient for ensuring worker safety. Continuous environmental monitoring and strict adherence to personal protective equipment (PPE) protocols are crucial for reducing occupational hazards. Enhanced regulatory guidelines and comprehensive training programs are recommended to improve safety practices in greenhouse environments. Future studies should expand monitoring efforts across various settings to better inform occupational health policies.